Influence of silica source in the catalytic activity and heterogenity of mesoporous vanadosilicates - Shylesh, S.; Mirajkar, Subhash P.; Singh, A. P. (Journal of Molecular Catalysis A-Chemical, 2005)
Vanadium-substituted ordered mesoporous silicates (V-OMS) were synthesized hydrothermally using two common silica sources, viz. fumed silica and tetraethyl orthosilicate, and their surface properties and catalytic activities were evaluated in the liquid phase oxidation of 1-napthol using aqueous H2O2 as an oxidant. The catalysts were characterized by XRD, N-2, adsorption-desorption, DRUV-vis and TPR to evaluate the mesostructural ordering and the local environment of vanadium in the MCM-41 matrix. Characterization data of the fresh calcined catalysts reveal a more ordered hexagonal structure for the V-MCM-41 catalyst prepared by using tetraethyl orthosilicate as the silica source while spent catalyst showed that the material is less stable than the V-MCM-41 catalyst prepared by using fumed silica as the silica source. Further, the observed differences in the selectivity behavior of extracted and calcined forms of both vanadium catalysts shows that the treatment conditions had a decisive role in the formation of extra framework metal species and further in the mesoscopic structural ordering. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: 1-napthol; MCM-41; Mesoporous; Oxidation; Vanadium

Copper(II) ion exchanged A1SBA-15: a versatile catalyst for intermolecular hydroamination of terminal alkynes with aromatic amines - Shanbhag, Ganapati V.; Joseph, Trissa; Halligudi, Shivaraj B. (Journal of Catalysis, 2007)
The hydroarnination reaction offers a very attractive route for the synthesis of alkylated amines and their derivatives with no byproduct formation. AISBA-15 was synthesized by isomorphous substitution of aluminum into the framework of SBA-15, which induces the Bronsted acid sites, and these were exchanged with metal ions such as Cu2+, Zn2+, and Pd2+. The catalysts were characterized by XRD, N-2-sOrption, SEM, TEM, acidity measurements by FT-IR pyridine adsorption, H-2-TPR, (27)AI MAS NMR, and Si-29 MAS NMR. Hydroamination of phenylacetylene (PhAc) with 2,4-xylidine has been used as a test reaction, which gave N-(1-phenylethylidene)-2,4-dimethylaniline with no byproduct formation. CuAlSBA-15 and CuAIMCM-41 showed around three times greater activity in hydroamination of PhAc compared with Cu-clay and Cu-beta, due to the moderate Lewis acidity of Cu2+ present in mesoporous supports. The performance of the CuAlSBA-15 was also determined with different alkynes and amines to evaluate the catalyst's general applicability in hydroamination reactions. (c) 2007 Elsevier Inc. All rights reserved.
Keywords: A1SBA-15; addition; alkyne; Amine; Copper catalyst; heterogeneous; hydroamination; ion exchange; Mesoporous

Chemoselective synthesis of beta-amino acid derivatives by hydroamination of activated olefins using AISBA-15 catalyst prepared by post-synthetic treatment - Shanbhag, Ganapati V.; Kumbar, S. M.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2008)
beta-Amino acid derivatives have a wide variety of applications viz. in the synthesis of peptide analogues, precursor for amino alcohols, optically active amino acids, lactums and diamines. Chemoselective anti-Markovnikov hydroamination reaction of activated olefins was effectively used to synthesize beta-amino acid derivatives using AlSBA-15 and AlMCM-41 catalysts. These catalysts with different Si/Al ratios were synthesized by isomorphous substitution of aluminium into the framework of SBA-15, which induces the Bronsted and Lewis acid sites. The structural integrity of the catalysts was established by characterizing with XRD, N-2-sorption, TEM, NH3-TPD Al-27 MAS NMR and Si-29 MAS NMR techniques. Hydroamination of ethyl acrylate with aniline was used as a test reaction, which gave N-[2-(ethoxycarbonyl)ethyl] aniline with high selectivity. The performance of AlSBA-15 catalyst was also determined with different acrylates and amines to know the general applicability of the catalyst in hydroamination reactions. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: acrylate; activated olefin; addition; AlMCM-41; AlSBA-15; Amine; beta-amino acid; Catalyst; hydroamination; Mesoporous

Tin incorporated periodic mesoporous organosilicas (Sn-PMOs): synthesis, characterization, and catalytic activity in the epoxidation reaction of olefins - Sisodiya, Sheetal; Shylesh, S.; Singh, A. P. (Catalysis Communications, 2011)
Tin incorporated mesoporous organosilicas (Sn-PMO) having uniform hexagonal arrangements were prepared using alkyl trimethylammonium bromide surfactants under basic reaction conditions. Characterization techniques revealed that the structural ordering, morphology, and the percentage of tin incorporation depend critically on the hydrophobic chain length of surfactants. The Sn-PMO samples are thermally stable up to 500 degrees C under air atmosphere and were hydrothermally stable up to 100 h in boiling water. The organotinsilicates showed excellent catalytic activity and reusability in the epoxidation of norbornene and ciscyclooctene than an Sn-MCM-41 due to organic groups in the frame wall positions and the better accessibility of reactants to the active sites. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: epoxidation; Hydrothermal stability; Mesoporous; Organosilica; Sn-MCM-41; Sn-PMO

Confinement of zinc oxide nanoparticles in ordered mesoporous silica MCM-41 - Lihitkar, P. B.; Violet, Samuel; Shirolkar, Mandar; Singh, Jai; Srivastava, O. N.; Naik, R. H.; Kulkarni, S. K. (Materials Chemistry and Physics, 2012)
Mesoporous silica (MS) and zinc loaded MS composites have been synthesized and characterized using high resolution transmission electron microscopy, X-ray diffraction, UV-visible spectroscopy, photoluminescence spectroscopy, N-2 adsorption-desorption isotherms, X-ray photoelectron spectroscopy and Fourier transform infrared spectroscopy. Thermal treatment of the zinc loaded MS composite lead to the formation of ZnO-MS composite. The well ordered uniform pore structure of MS (pore size similar to 3.4 nm) is found to remain stable even after 30% Zn loading albeit decrease in the pore size 1.2 nm indicates the formation of ZnO inside the pores. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Defect; Energy spectroscopy for chemical analysis (ESCA); Mesoporous; Photoluminescence spectroscopy; Surface properties

Chiral (VO)-O-IV-Sal-Indanol complex over modified SBA-15: an efficient, reusable enantioselective catalyst for asymmetric sulfoxidation reaction - Lazar, Anish; Sharma, Priti; Singh, A. P. (Microporous and Mesoporous Materials, 2013)
A reusable, mesoporous, heterogeneous vanadium complex, (VO)-O-IV-Sal-Ind-SBA-15 has been synthesized first time from (1R,2S)-(+)-Cis-1-amino-2-indanol for enantioselective sulfoxidation reaction. The physico-chemical properties of the functionalized catalyst were analyzed by a series of characterization techniques like XRD, N-2 sorption measurement isotherm, TEM, FT-IR, XPS, EPR, DRS UV-Visible, ICP-OES and solid & liquid state C-13, Si-29 and V-51 NMR spectroscopy. Powder X-ray diffraction patterns, TEM and N-2 physisorption analysis confirmed the retention of mesoporous structure after various modifications. Solid-state NMR (C-13 CP-MAS NMR, Si-29 MAS NMR) and FT-IR analysis certified the integrity of organo-catalyst residing inside the pore channels of the mesoporous support. Further, XPS, EPR, V-51 NMR and DRS UV-Visible analyses help to find out the oxidation state and coordination environment of vanadium in (VO)-O-IV-Sal-Ind-SBA-15. Catalytic evaluation in asymmetric sulfoxidation reaction of sulfides indicated that VOIV-Sal-Ind-SBA-15 exhibited higher catalytic activity, stability, reusability and comparable enantioselectivity than SBA-15, PrNH2-SBA-15, neat (VO)-O-IV-Sal-Indanol complex and without catalyst. The effect of different catalysts, temperature, solvents and substrates on sulfoxidation reaction were examined in order to optimize the conversion and enantioselectivity of thioanisoles to sulfoxides. Crown Copyright (C) 2012 Published by Elsevier Inc. All rights reserved.
Keywords: (1R; 2S)-(+)-Cis-1-amino-2-indanol; Asymmetric sulfoxidation; Heterogeneous vanadium complex; Mesoporous; Thioanisole

Mesoporous shell@macroporous core aluminosilicates as sustainable nanocatalysts for direct N-alkylation of amines - Sekhar, Anandakumari C. Sunil; Ashokkumar, Anumol Erumpukuthickal; Cygnet, Choorapoikayil T.; Lakshmi, Saseendranpillai Vidhya; Deepak, Francis Leonard; Vinod, Chathakudath P. (Chemnanomat, 2018)
Aluminosilicate spheres with a macroporous core and mesoporous shell (Si/Al ratio of 11) is synthesised by a sol-gel method utilizing cetyltrimethyl ammonium bromide (CTAB) as a structure directing agent in basic medium. The selective incorporation of aluminium in the silica matrix results in the formation of aluminosilicates with an overall acidity of 0.32mmol/g with interconnected pores. Direct N-alkylation reaction is a prototype of C-N bond formation reaction and meso- macroporous aluminosilicate is shown to catalyze this reaction with excellent yield. The catalyst is tested and found sustainable for five catalytic cycles even without any high temperature regeneration step.
Keywords: Aluminosilicates; macroporous; Mesoporous; N-alkylation; nanocatalysis

MWCNTs-ZnO-SiO2 mesoporous nano-hybrid materials for CO2 capture - Jena, Kishore K.; Panda, Amulya Prasad; Verma, Savita; Mani, Ganesh Kumar; Swain, S. K.; Alhassan, Saeed M. (Journal of Alloys and Compounds, 2019)
Carbon nanostructures and metal nanoparticles based nanohybrid materials have been established as one of advantageous materials for various applications. Here, we present hydrothermal and sol-gel process at low temperature for the synthesis of (3-Aminopropyl) triethoxysilane (APTES)-ZnO-multi-walled carbon nanotubes (MWCNTs) mesoporous nanohybrid materials. TEM and XPS measurements show that uniform size and quasi-spherical ZnO nanoparticles were anchored to the surface of the MWCNTs. SEM observation exhibits that the aggregation of ZnO nanoparticles is greatly reduced due to the steric repulsion of grafted organic groups. The maximum CO2 adsorption capacity at 273 K was 1.32 mmol/g for MWCNTs-APTES-ZnO-B nanohybrid. An increase in the density of ZnO nanoparticles on the surface of MWCNTs resulted in a higher affinity towards CO2 at low pressure. This work provides new research directions for making further advances toward practical utilization of MWCNTs-based CO2 adsorbents. (C) 2019 Published by Elsevier B.V.
Keywords: CO2 capture; Mesoporous; MWCNTs; Nanohybrid; TEM; XPS

Superior humidity sensor and photodetector of mesoporous ZnO nanosheets at room temperature - Gupta, Shobhnath P.; Pawbake, Amit S.; Sathe, Bhaskar R.; Late, Dattatray J.; Walke, Pravin S. (Sensors and Actuators B-Chemical, 2019)
Miniaturized sensor technology is vastly demanding multifunctional materials to fulfill many requirements simultaneously; instead of integrating various sensors into a single device. Efficient operation of these miniaturized sensors at room temperature is highly feasible and cost-effective. The humidity sensing and photodetection is precise merit of sensing in special usage like artificial skin. Sensitivity enhancement in both humidity and photodetection required the high surface area for adsorption as well as a high charge transfer mechanism. The two dimensional (2D) zinc oxide nanosheets (ZnO NS) is the ultimate structure for dimensionally confined transport properties owing to the specific surface atomic configuration that results in high sensitivity, low operating temperature, fast response and recovery, and improved selectivity. Furthermore, introducing porosity into 2D nanostructures has opened new opportunities to enhance the efficiency of sensors and detectors via increasing large surface area and tunable physical and chemical properties. Here we report preparation of mesoporous and highly crystalline 2D ZnO NS by a single step, template free, cost-effective chemical method. The structural and morphological characterizations of ZnO NS are carried out using XRD, FESEM, XPS, TEM respectively. The high-resolution TEM images emphasize sheet-like morphology with a thickness of around 18-22 nm. Further the mesoporous ZnO NS (MZNS) with the pore size between 5-10 nm are achieved by simple heat-treatment. XPS and PL study is confirming the oxygen deficiency in MZNS. The MZNS exhibits an excellent responsivity than PZNS with a fast response and rapid recovery time of 25 s and 5 s respectively along with good cyclic stability which is highly crucial for smart humidity sensor. Furthermore, it considerably enhances photo-sensor performance than pristine ZnO NS (PZNS) with (similar to)1 s response time as well as (similar to)1 s recovery time along with better stability. These promising results illustrate the great potential of MZNS for next-generation humidity sensors and photodetectors.
Keywords: humidity sensor; Mesoporous; nanosheets; Photo-detector